Respostas

A melhor resposta!
  • Usuário do Brainly
2013-06-01T13:48:12-03:00

a) Temos que:

 

\dfrac{3}{5}\times\left(\dfrac{1}{3}-\dfrac{1}{2}\right)

 

=\dfrac{3}{5}\times\left(\dfrac{2-3}{6}\right)

 

=\dfrac{3}{5}\times\dfrac{-1}{6}=\dfrac{-3}{30}=\dfrac{-1}{10}


b) Temos que:

 

\dfrac{-2}{9}\times\left(\dfrac{1}{4}+\dfrac{1}{5}\right)

 

=\dfrac{-2}{9}\times\left(\dfrac{5+4}{20}\right)

 

=\dfrac{-2}{9}\times\dfrac{9}{20}=\dfrac{-18}{180}=\dfrac{-1}{10}

 

c) Temos que:

 

\dfrac{2}{5}-\dfrac{8}{3}\times\left(\dfrac{1}{2}\right)^3+\dfrac{3}{4}

 

=\dfrac{2}{5}-\dfrac{8}{3}\times\dfrac{1}{8}+\dfrac{3}{4}

 

=\dfrac{2}{5}-\dfrac{1}{3}+\dfrac{3}{4}

 

=\dfrac{24-20+45}{60}=\dfrac{49}{60}


d) Temos que:

 

\dfrac{-7}{9}\times\left(\dfrac{2}{3}-\dfrac{4}{5}\times5\right)

 

=\dfrac{-7}{9}\times\left(\dfrac{2}{3}-4\right)

 

=\dfrac{-7}{9}\times\left(\dfrac{2-12}{12}\right)

 

=\dfrac{-7}{9}\times\dfrac{-10}{12}

 

=\dfrac{70}{108}=\dfrac{35}{54}

2 5 2